Introduction to theory of canonical matrices - Turnbull, H. W.; Aitken, A. C. (New York Dover Publications, 1961)
Thorough and self-contained, this penetrating study of the theory of canonical matrices presents a detailed consideration of all the theory's principal features -- from definitions and fundamental properties of matrices to the practical applications of their reduction to canonical forms. Beginning with matrix multiplication, reciprocals, and partitioned matrices, the text proceeds to elementary transformations and bilinear and quadratic forms.
Keywords: Mathematics matrices; Applied mathematics